1978
DOI: 10.1093/bja/50.11.1113
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacodynamic Model for Pancuronium

Abstract: It has been demonstrated that a simple two-compartment kinetic model may account for the changes in plasma concentration of pancuronium after i.v. administration. However, it can be shown that this simple model does not account satisfactory for the observed changes in muscle twitch response. By the addition of a receptor (biophase) compartment, twitch response can be reconciled with model behavior and the characteristics resemble those predicted by animal studies. The complete model is applied to the problem o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
3

Year Published

1985
1985
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(80 citation statements)
references
References 11 publications
3
74
0
3
Order By: Relevance
“…The pharmacokinetic data for pancuronium obtained by Hull et al 13 were applied to the conditions of the present study and calculations of predicted pancuronium concentration at the neuromuscular junction were performed on an IBM personal computer. These calculations demonstrated that the concentration of pancuronium sufficient to produce paralysis did occur earlier after divided dose administration.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic data for pancuronium obtained by Hull et al 13 were applied to the conditions of the present study and calculations of predicted pancuronium concentration at the neuromuscular junction were performed on an IBM personal computer. These calculations demonstrated that the concentration of pancuronium sufficient to produce paralysis did occur earlier after divided dose administration.…”
Section: Discussionmentioning
confidence: 99%
“…This signifies that it is necessary to use a variable infusion rate K(t) to maintain the concentration in the therapeutic margin. However, the drug concentrations are not an adequate basis for therapeutic decision when the plasma is not the site of drug effect (5,6). The The curves of Figure 5 demonstrate the influence ofthe administration time.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the opioid was assumed to relate to C e at a theoretical effect compartment. [20][21][22] Equilibration between this effect compartment and the plasma compartment was assumed to follow a first-order transfer process with a rate constant k e0 . Thus, the time course of C e , C e (t), is described by…”
Section: Methodsmentioning
confidence: 99%